Optimasi Jaringan Internet Di Gedung Teknik Elektro Politeknik Negeri Sriwijaya - Suci Tri Lestari; Suroso Suroso; Ibnu Ziad (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2019)
Nowadays wireless communication has become a basic necessity for the community. WiFi (wireless fidelity) One of them, which is a local network that uses an electromagnetic signal that works at a frequency of 2.4 GHz. Tool to implement WiFi is Access point (AP). The toughest bully in the world of WiFi is known for interference. Interference is the use of the same frequency or channel on a network. Interference can cause service quality to decline so that it is less optimal in its usage, therefore the optimization needs to the network so that users can use the network without constraints. From the results of the research that has been done, the optimization is done by evaluating the selection of the channel from each access point studied with the access point that was concluded that the optimization of the results of all access points experienced Improved signal quality as in AP 1 prior to optimized (-64.0) dBm to (-56.0) dBm category good and after optimized (-56.0) dBm to (-48) dBm category excellent.